Large-extension osteosarcoma with involvement of multiple maxillofacial structures: a rare case report (Research, Society and Development, 2020)
Background: Osteosarcoma is a malignant neoplasm that occurs most often in long bones, with the head and neck region being rarely affected, accounting for less than 1% of all cancers in this region. Objective: To report a rare case of a large-extension osteosarcoma with emphasis on its clinical and diagnostic aspects. Case presentation: A 43-year-old woman presenting an intraoral exophytic lesion with involvement of other maxillofacial structures, such as nostril, zygoma and orbit. Despite the initial clinical diagnosis of actinomycosis, an incisional biopsy confirmed the histopathological diagnosis of osteosarcoma, showing a wide morphological variety. Conclusion: This case highlights the importance of clinical and histopathological findings for the correct diagnosis of osteosarcoma. Moreover, it shows that, although surgical resection is the primary treatment for this neoplasia, depending on the extent of the tumor and its proximity to vital anatomical structures, the most appropriate conduct is not always feasible.